Magmatism and Geothermal Potential in Pandan Volcano East Java Indonesia - Isao Takashima; Dwi Fitri Yudiantoro (Jurnal Mineral, Energi dan Lingkungan, 2018)
Pandan volcano is a volcano formed on Tertiary sedimentary rocks from the Kendeng zone deposited in the basin of East Java. In addition to generating petroleum potentials, such as Cepu and Bojonegoro oil fields, this area also generates geothermal potential. As a source of heat from the geothermal system is igneous rock formed from the magmatism process. The type of rock formed by the process of magmatism in the Pandan geothermal system is basaltic-andesitic and hornblende andesite are medium-high K calk alkaline affinity located in the island arc. The interaction of hot rock from post magmatism process with hydrothermal fluid resulted in the manifestation of hot springs and calcite travertine in the study area. Prediction of the subsurface temperature of hot water from geothermometer silica analysis contained in Banyukuning and Jarikasinan show cristobalite Beta equilibrium (70oC) and quartz temperature (120oC). To study about magmatism and geothermal fluid using petrographic method and petrochemical analysis (X-ray fluorescence spectrometry method) to the sample of igneous rock. While to study the fluid type and geothermometer of geothermal fluid using data from previous researchers. This research study is expected to provide additional information on the field of geothermal and magmatism in this area.